An Integrated Reading/Writing Instruction for Better EFL Trainees at the Teachers Training School of Constantine (ENSC) - LABIOD, Ahlem (Journal of Human Sciences, 2017)
Several studies acknowledge the importance of integrating reading and writing in one subject but few EFL contexts seem to consider this claim. Teachers Training School of Constantine (ENSC), Algeria, is a standing case where these two language skills are till nowadays taught as discrete subjects neglecting new ways of a more meaningful learning. This paper reports the findings of an empirical study which investigates the impact of the implementation of an integrated reading/writing instruction through the use of reading response journals (RRJs) on trainees’ achievements in these two skills. An experimental design is used where a treatment intervention is applied preceded by a pretest and followed by a posttest. A quantitative analysis is conducted confirming that teaching EFL reading and writing in an integrated way through RRJs helped enhance trainees’ level in both skills.